The shape of data in the digital humanities modeling texts and text-based resources - Flanders, Julia; Jannidis, Fotis (London ; New York : Routledge, 2019)
"Data and its technologies now play a large and growing role in humanities research and teaching. This book addresses the needs of humanities scholars who seek deeper expertise in the area of data modeling and representation. The authors, all experts in digital humanities, offer a clear explanation of key technical principles, a grounded discussion of case studies, and an exploration of important theoretical concerns. The book opens with an orientation, giving the reader a history of data modeling in the humanities and a grounding in the technical concepts necessary to understand and engage with the second part of the book. The second part of the book is a wide-ranging exploration of topics central for a deeper understanding of data modeling in digital humanities. Chapters cover data modeling standards and the role they play in shaping digital humanities practice, traditional forms of modeling in the humanities and how they have been transformed by digital approaches, ontologies which seek to anchor meaning in digital humanities resources, and how data models inhabit the other analytical tools used in digital humanities research. It concludes with a glossary chapter that explains specific terms and concepts for data modeling in the digital humanities context. This book is a unique and invaluable resource for teaching and practising data modeling in a digital humanities context"--
Part 1: Orientation. Data modeling in a digital humanities context : an introduction / Julia Flanders and Fotis Jannidis -- A gentle introduction to data modeling / Fotis Jannidis and Julia Flanders -- Part 2: Topics in digital humanities data modeling. How modeling standards evolve : the case of the TEI / Lou Burnard -- How subjective is your model? / Elena Pierazzo -- Modeling space in historical texts / Ian Gregory, Christopher Donaldson, Andrew Hardie, and Paul Rayson -- Modeling time / Benjamin Schmidt -- Visualizing information / Isabel Meirelles -- Ontologies and data modeling / Øyvind Eide and Christian-Emil Smith Ore -- Where semantics lies / Stephen Ramsay -- Constraint / Julia Flanders, Fotis Jannidis, and Wendell Piez -- Modeling and annotating complex data structures / Piotr Banski and Andreas Witt -- Linguistic and computational modeling in language science / Elke Teich and Peter Fankhauser -- Algorithmic modeling : or, modeling data we do not yet understand / Ted Underwood -- Modeling the actual, simulating the possible / Willard McCarty -- Playing for keeps : the role of modeling in the humanities / C.M. Sperberg-McQueen -- Part 3: Back matter. Glossary / Julia Flanders and Fotis Jannidis.
Literaturangaben
Keywords: Digital Humanities; Aufsatzsammlung